1977
DOI: 10.1136/hrt.39.9.988
|View full text |Cite
|
Sign up to set email alerts
|

Natural history and evaluation of ST segment changes and MB CK release in acute myocardial infarction.

Abstract: The experimental evidence relating ST segment elevation in the electrocardiogram to the progress and extent of ischaemic myocardial damage is discussed. There are difficulties in applying this to patients: the reproducibility of praecordial mapping was tested using a multiple analysis of variance. This showed that factors such as time after the onset of myocardial infarction and posture can affect measurements of sigmaST elevation significantly. There was a pattern of changes in segmaST elevation and of change… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0

Year Published

1978
1978
1987
1987

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 35 publications
(6 citation statements)
references
References 14 publications
0
6
0
Order By: Relevance
“…Blomqvist et al (1975) showed that there was a significant correlation between EST and the area of an infarct as determined by pyrophosphate scan. By contrast, Norris et al (1976), Thompson and Katavatis (1976), and Selwyn et al (1977a) showed no correlation or at best weak correlation between ST segment elevation and peak or total plasma enzyme.…”
Section: St Segment Elevationmentioning
confidence: 72%
See 1 more Smart Citation
“…Blomqvist et al (1975) showed that there was a significant correlation between EST and the area of an infarct as determined by pyrophosphate scan. By contrast, Norris et al (1976), Thompson and Katavatis (1976), and Selwyn et al (1977a) showed no correlation or at best weak correlation between ST segment elevation and peak or total plasma enzyme.…”
Section: St Segment Elevationmentioning
confidence: 72%
“…Secondly, variations in chest shape and size and localisation of infarction may lead to differences between patients. Thirdly, ST segment elevation is known to increase or decrease rapidly in some patients (Selwyn et al, 1977a) and variable intervals between onset of pain and time of electrocardiographic recording will introduce further error. To minimise this source of error we have taken recordings at regular intervals in all our patients.…”
Section: St Segment Elevationmentioning
confidence: 99%
“…when using the same lead. It has recently been shown, using the praecordial mapping technique in patients with anterior AMI, that the maximal ST elevation occurs one hour after the onset of chest pains (13). However, animal experiments have demonstrated that the maximal ST elevation, when using epicardial electrodes, occurs already 5-15 min after the occlusion (6,10).…”
Section: Discussionmentioning
confidence: 99%
“…Recent investigations suggest that the most pronounced development in the infarction process in man takes place within the first 24 hours after the onset of symptoms ( I , 13,14). This makes it essential to know the exact time sequence of the electrocardiographic (ECG) changes in the early phase of acute myocardial infarction (AMI).…”
mentioning
confidence: 99%
“…The ST segment was considered to be depressed if there was 1 00 mm or more of shift for at least 0-08 s (Mason and Likar, 1966). ST segment elevation was measured 0-06 s from the end of the QRS complex (Selwyn et al, 1977b), and was ignored if less than 1 mm. None of the patients had ST segments which at rest lay above or below the isoelectric line.…”
Section: Interpretation Of Recordsmentioning
confidence: 99%